2022
DOI: 10.1049/rpg2.12450
|View full text |Cite
|
Sign up to set email alerts
|

Dual mechanical port power distribution in dual rotor permanent magnet flux switching generator for counter‐rotating wind turbine applications

Abstract: In this paper, a novel dual mechanical port dual rotor counter-rotating permanent magnet flux switching generator (DMPDRCR-PMFSG) for wind turbine applications is proposed. Power distribution between the inner and outer rotors of the proposed DMPDRCR-PMFSG that contributes to the cumulative output power is investigated. The proposed DMPDRCR-PMFSG shares a stator connected back-to-back through flux bridge. The flux bridge physically isolates the armature winding of the inner and outer ports. Furthermore, the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 33 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Regarding the electric generators for WECS, Booker et al (2010) andHabash et al (2011) proposed the use of counter-rotating electrical generators for wind turbine applications in urban areas, which have a mobile rotor (GR) and mobile stator (GS) rotating in opposite directions due to their increased energy performance compared to the conventional (with a fixed stator GS) generators. The counter-rotating generator was further investigated in terms of performance and rotor topology by Kutt et al (2020), Egorov et al (2021), andMirnikjoo et al (2021) and in terms of optimized system configuration with counter-rotating rotors (Mirnikjoo et al, 2020;Ullah et al, 2022a;Ullah et al, 2022b). Cho et al (2017) analyzedthe performance and control of a WECS with counterrotating rotors and counter-rotating generator and concluded that this configuration can lower the tip speed ratio at which the power curve attains its maximum almost by half in comparison to the single-rotor system.…”
mentioning
confidence: 99%
“…Regarding the electric generators for WECS, Booker et al (2010) andHabash et al (2011) proposed the use of counter-rotating electrical generators for wind turbine applications in urban areas, which have a mobile rotor (GR) and mobile stator (GS) rotating in opposite directions due to their increased energy performance compared to the conventional (with a fixed stator GS) generators. The counter-rotating generator was further investigated in terms of performance and rotor topology by Kutt et al (2020), Egorov et al (2021), andMirnikjoo et al (2021) and in terms of optimized system configuration with counter-rotating rotors (Mirnikjoo et al, 2020;Ullah et al, 2022a;Ullah et al, 2022b). Cho et al (2017) analyzedthe performance and control of a WECS with counterrotating rotors and counter-rotating generator and concluded that this configuration can lower the tip speed ratio at which the power curve attains its maximum almost by half in comparison to the single-rotor system.…”
mentioning
confidence: 99%